TANTANGAN PEMBELAJARAN IPAS DI KELAS IV SDN 56/1 DESA ARO: MINIMNYA MEDIA PEMBELAJARAN, DAN SUASANA BELAJAR YANG KURANG KONDUSIF - Liana Fitri; Ulya; Ibremi Br Ginting; Intan Marsela; Khoirunnisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This observation discusses the challenges faced in teaching Natural and Social Sciences (IPAS) to fourth-grade students at SDN 56/1 Desa Aro. The main focus of this observation is the limited availability of learning media such as projectors and practical teaching aids, as well as the less conducive classroom atmosphere caused by students’ low interest and attention. The purpose of this observation is to analyze the main factors of these problems and their impact on students’ motivation and learning outcomes. The methods used include observation, interviews with the homeroom teacher, and documentation during the learning process. The results show that the lack of learning media makes it difficult for teachers to deliver material in an engaging way, causing students to become easily bored. In addition, the unsupportive learning environment also affects students’ enthusiasm and concentration. Based on these observations, efforts are needed to improve learning facilities and develop innovative teaching strategies to create a more active and enjoyable classroom atmosphere.